ANALISIS DAN PERANCANGAN APLIKASI PEMANTAUAN PROSES PEMBIMBINGAN KERJA PRAKTIK PADA INSTITUT BISNIS DAN INFORMATIKA STIKOM SURABAYA - Novand Dwiki Harliansyah; Asteria B. Tjandrarini; Julianto Lemantara (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Institut Bisnis dan Informatika Stikom Surabaya (Stikom Surabaya) is one of the private universities in Surabaya within the scope of Kopertis VII. The problems focus in Stikom Surabaya is on Technical Implementing Units (UPT) that responsible in serving the practical work. Currently, the existing system has not run well, so that information is not conveyed to Head of Study Program, Apprenticeship Supervisors, and Lecturer can’t monitor the progress of student who do practical work. Students of practical work who is too long in the implementation so that when they parents ask about the workmanship to Head of Study Program, Apprenticeship Supervisors, and Lecturer, they can’t said about the truth with the existing practical work . Mentoring schedule of apprenticesjip supervisor is not easy to be known by students so they have to meet apprenticeship supervisor for asking about the schedule. The students do not always write down the due date and the description of mentoring process directly on mentoring form. The problem above has been solved by creating analysis and design of monitoring application of work guidance at Institut Bisnis dan Informatika Stikom Surabaya. This application has the required data function, generating information and reports related to practical work. The application provides notifications by e-mail to students, academic advisor, apprenticeship supervisor, and PPKP staff. Based on testing results, analysis and deseign of the application, the resulting report is the progress development practical work, progress of the extention students, and practical work guidance card. Application also produce information related to practical work.